Produtividade e qualidade de cultivares de batata em função de doses de NPK - Queiroz, Angélica Araújo (2011)
The demand for fertilizer on the potato crop is the largest among the crops grown in Brazil, ranging from 2.3 to 2.8 t ha-1. Thus, the purpose of this study was to evaluate the yield of potato tubers Ágata, Atlantic Asterix and depending on the levels of N, P and K applied at planting. The experiments were performed and conducted in the municipality of São Gotardo, Perdizes, Serra do Salitre, and Itajubá in Minas Gerais, in the rainy season of 2009 and dry season of 2010. The experimental design was randomized blocks with four replications and five doses. Three experiments were conducted simultaneously, one for each nutrient (N, P and K). Doses tested were 0, 70, 140, 210 and 240 kg N ha-1, 0, 150.300, 450 and 600 kg K2O ha-1 and 0, 200, 400, 600 and 800 kg ha-1 P2O5. On the soil were added at planting five doses of the nutrient studied, combined with doses considered standard for the potato crop, plus 30 kg ha-1 of a source of micronutrients. At 30 DAP, the leaves were sampled from each plot and analyzed for content of macro and micronutrients, taking the DRIS for culture. At the end of the experiments the tubers were harvested, graded, weighed and calculated the productivity of the useful area of the plots. It concluded that to grow Ágata yield was influenced by P levels in the two locations studied. The N increased productivity in São Gotardo until the dose of 219 kg N ha-1 with a yield of 47.6 t ha-1 of tubers and K fertilization did not affect the tuber yield in any of the locations. According to the DRIS, the order of failure in areas of high productivity was: K> S> Zn> Mg = P = B> Cu> Ca> N = Mn> Fe, and the order of failure in areas of low productivity was: Cu> Fe> Mg> N> Mn> B> S> P> K> Zn> Ca in the São Gotardo and Itajubá the order of failure in areas of high productivity was: Zn> Mg> Cu = Mn = P> B> N> S = Fe> K> Ca, and the order of failure in areas of low productivity was: B> Ca> Mg> Mn> Fe> Zn = N> S> P = Cu> K. Atlantic cultivar productivity of tubers was not influenced by the studied doses of N, P and K, however, with the DRIS established the order of failure in areas of high productivity: Cu> Ca = Zn> Fe> N> Mn> K> Mg = P> S = B, and the order of failure in areas of low productivity: Ca> K> Zn> S> N> Cu> P> B> Mg = Fe> Mn. The cultivar Asterix was not influenced by the levels of P and K, studied, and there was an increase in tuber yield in relation to the levels of N applied up to a dose of 173 kg ha-1 N and DRIS, we can establish the order of failure in areas of high productivity: Ca> Mn> P> S> Zn = Cu> K> N> B> Fe> Mg, and order failure.